NLRP3 Inflammasome Activation: A Therapeutic Target for Cerebral Ischemia–Reperfusion Injury - Wang, Lixia; Ren, Wei; Wu, Qingjuan; Liu, Tianzhu; Wei, Ying; Ding, Jiru; Zhou, Chen; Xu, Houping; Yang, Sijin (Frontiers in Molecular Neuroscience, 2022)
Millions of patients are suffering from ischemic stroke, it is urgent to figure out the pathogenesis of cerebral ischemia–reperfusion (I/R) injury in order to find an effective cure. After I/R injury, pro-inflammatory cytokines especially interleukin-1β (IL-1β) upregulates in ischemic brain cells, such as microglia and neuron. To ameliorate the inflammation after cerebral I/R injury, nucleotide-binding oligomerization domain (NOD), leucine-rich repeat (LRR), and pyrin domain-containing protein 3 (NLRP3) inflammasome is well-investigated. NLRP3 inflammasomes are complicated protein complexes that are activated by endogenous and exogenous danger signals to participate in the inflammatory response. The assembly and activation of the NLRP3 inflammasome lead to the caspase-1-dependent release of pro-inflammatory cytokines, such as interleukin (IL)-1β and IL-18. Furthermore, pyroptosis is a pro-inflammatory cell death that occurs in a dependent manner on NLRP3 inflammasomes after cerebral I/R injury. In this review, we summarized the assembly and activation of NLRP3 inflammasome; moreover, we also concluded the pivotal role of NLRP3 inflammasome and inhibitors, targeting the NLRP3 inflammasome in cerebral I/R injury.